Mesial Migration of Lower Molars in Relation to Facial Growth and Eruption - Richardson Margaret E. (Australasian Orthodontic Journal, 1996)
Mesial migration of teeth in the huccal segments is a well recognised phenomenon in the human dentition. Its aetiology is not fully understood. It has heen suggested that it is, to some extent, dependent on growth changes in the lower face.